1996
DOI: 10.1542/peds.97.3.375
|View full text |Cite
|
Sign up to set email alerts
|

High-dose Corticotropin (ACTH) Versus Prednisone for Infantile Spasms: A Prospective, Randomized, Blinded Study

Abstract: Objective. To compare the efficacy of corticotropin (ACTH) (150 U/m2/day) and prednisone (2 mg/kg/day), given for 2 weeks, in suppressing clinical spasms and hypsarrhythmic electroencephalogram (EEG) in infantile spasms (IS). ACTH and prednisone are standard treatments for IS. ACTH at high doses causes severe dose- and duration-dependent side effects, but may be superior to prednisone, based on retrospective or uncontrolled studies. Blinded prospective studies have shown equal efficacy of prednisone and low-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(70 citation statements)
references
References 25 publications
3
65
0
2
Order By: Relevance
“…In addition, clobazam used in our study might be a potentially effective adjunctive drug for West syndrome [37]. It is worth mentioning that similar results were reached in some old studies in the case of highdose ACTH monotherapy and combination of low-dose ACTH and pyridoxine [23,38]. According to some authors, increasing the dose of ACTH does not necessarily result in better seizures control [39].…”
Section: Discussionsupporting
confidence: 81%
“…In addition, clobazam used in our study might be a potentially effective adjunctive drug for West syndrome [37]. It is worth mentioning that similar results were reached in some old studies in the case of highdose ACTH monotherapy and combination of low-dose ACTH and pyridoxine [23,38]. According to some authors, increasing the dose of ACTH does not necessarily result in better seizures control [39].…”
Section: Discussionsupporting
confidence: 81%
“…Six RCTs that compared ACTH with oral corticosteroids for the treatment of ISs, with 323 participants included, met our inclusion criteria ( 5 , 7 , 9 , 11 , 12 , 15 ). Three of these RCTs, namely, Hrachovy et al ( 5 ), Baram et al ( 7 ), and Sardar et al ( 15 ), used low-dose corticosteroids (2 mg/kg/day of prednisone or prednisolone). The other three RCTs, namely, Lux et al ( 9 ), Wanigasinghe et al ( 11 ), and Gowda et al ( 12 ), applied high-dose prednisolone (4 mg/kg/day or 40–60 mg/day).…”
Section: Resultsmentioning
confidence: 99%
“…Six RCTs that compared ACTH with oral corticosteroids for the treatment of ISs, with 323 participants included, met our inclusion criteria (5,7,9,11,12,15). Three of these RCTs, namely, Hrachovy et al 9) was between hormonal therapy and VGB, so the secondary comparison of ACTH and prednisolone might be underpowered.…”
Section: Adrenocorticotrophic Hormone Vs Oral Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, overall efficacy in terms of complete response of prednisolone was observed in 43.5% of the total cases. Complete spasm freedom rates have been reported between 28% and 49% by different researchers with various dosage regimens of prednisolone [ 19 , 20 ]. We noted that infants in the high-dose group reported significantly better efficacy when compared to the low-dose group (complete response as 58.1% vs. 29.0%, p=0.0265).…”
Section: Discussionmentioning
confidence: 99%